Liste Des Gasteropodes Du Fleuve Saint-Laurent, Region De Gentilly - G. Vaillancourt; M. Dingemann (Hello World!, 1972)
In order to study the ecology of Gastropoda, the author's have made the qualitative and quantitative inventory of the waters of the St. Lawrence River in the Gentilly area. We give here the list of the 23 species which have been inventoried; they belong to the families Amnicolidae, Lymnaeidae, Physidae, Planorbidae, Pleuroceridae, Valvatidae and Viviparidae.